A Multi-Faceted Intervention to Reduce Obstetric Hemorrhage Risk at University Hospitals [01M]. (May 2020) - Cossler, Nancy; Liu, James H.; Katz, Tyler Jessica; Albertini, Megan; Furnari, Rosanne; Porter, Steven
Abstract : INTRODUCTION: We describe a systematic approach to mitigating obstetric hemorrhage risk at University Hospitals (UH), a northeast Ohio-based system of eighteen hospitals, including seven hospitals providing obstetric services and delivering approximately 8000 women/year. METHODS: From 2009-2015, obstetric hemorrhage (OBH) led to two maternal deaths and other harms in the form of excessive transfusions, ICU admissions, and hysterectomies as definitive treatment. OBH accounted for 11% of litigation costs ($7.4 M) during this period. To reduce harm associated with OBH, we implemented the following interventions: 1. Clinical Practice Guideline for management of anemia in pregnancy; 2. EMR field to capture hemorrhage risk factors and prompt type and cross on admission; 3. Mandating transfer of high risk patients for delivery at a tertiary care center; 4. Clinical Practice Guideline for management of OBH (including active management of third stage of labor); 5. Shifting from estimating to quantifying blood loss by weight; and 6. Standardization of OBH carts on all L&D units. RESULTS: From 2015-2017, there was: 40% increase in the number of patients admitted to L&D with hemoglobin >10 mg/dl; 68% decrease in the number of obstetric patients requiring transfusions of ≥four units of packed red blood cells; 77% decrease in the number of peri-partum hysterectomies; and 91% decrease in the number of patients admitted to ICU for OBH. There were no maternal deaths from OBH and no new suits or claims related to OBH between 2014 and 2018. CONCLUSION: This multifaceted intervention was associated with decreased patient harm and reduced litigation costs associated with obstetric hemorrhage.